Propensity Of Product Innovation In Malaysian Manufacturing Companies - Januiliali, Wan; Mohd Zain, Nordin (Asian Academy of Management (AAM), 1999)
The significance of new product development (NPD) to corporate success has drawn numerous studies over the last forty years. (NICB 1964; Cooper 1979, 1980; Calantone and Cooper 1981; Booz, Allen and Hamilton 1982; Maidique and Zirger 1984; Cooper and Kleinschmidt 1986, 1987, 1990). These studies have confirmed that new products are crucial to the financial well being of companies, making product development an inevitable function for most corporations.